Flowing liquid lithium plasma-facing components – Physics, technology and system analysis of the LiMIT system. (August 2017) - Ruzic, D.N.; Szott, M.; Sandoval, C.; Christenson, M.; Fiflis, P.; Hammouti, S.; Kalathiparambil, K.; Shchelkanov, I.; Andruczyk, D.; Stubbers, R.; Foster, C. Joel; Jurczyk, B.
Highlights: Liquid lithium offers a number of advantages over solid materials as a first wall PFC. Limitations still exist in using liquid lithium in large scale toroidal devices, which are addressed in this report. The primary limitations discussed include: 1) wetting, 2) heat flux handling, and 3) hydrogen isotope inventory management. Abstract: The use of low atomic number liquid metals has been shown to have the potential to solve many of the prevalent problems like erosion and radiation losses associated with the interaction of fusion plasma with the plasma facing component (PFC) structures in tokamaks. Since the first evidence of lithium increasing plasma performance in TFTR[1], the benefits of using lithium in fusion environments have been seen in many devices, including CDX-U[2], NSTX[3], LTX[4], and DIII-D[5] . While both fast flow and slow flow concepts have been studied with regards to liquid lithium first wall alternatives, this report will focus on efforts placed on fast flow research and will mainly focus on advancements in the LiMIT device that help to eliminate concerns over the broad use of liquid lithium. Due to the promising TFTR results along with results obtained at the University of Illinois at Urbana-Champaign[6], suitably designed trench structures holding liquid lithium could be an appropriate fast flow candidate for PFC modules in future fusion devices. There are four potential shortcomings of this approach: (1) Droplet ejection, (2) Wetting control, (3) Tritium retention, and (4) Limited heat flux handling. Droplet ejection is discussed in a companion publication[7], while this paper addresses the topics of wetting control and heat flux handling. Limitations in wetting and prevention of lithium creep (i.e. getting and keeping the lithium only where it should be) have been solved by laser-texturing the base material with extreme short laser pulses (pico – femto second) of high power (several 10 s of W). Micro- and nano-structuring results indicate that the textured substrates displayed significant change in their wetting properties, increasing the temperature needed to wet from 310 °C to 390 °C. Lastly, initial designs for the Lithium Metal Infused Trenches (LiMIT)[6] showed dryout above 3 MW/m 2, but new designs of the trench shaping show potential to be able to handle up to 10 MW/m 2 . Dryout is accompanied by lithium evaporation which is shown to mitigate the incident heat flux, which may be viewed as beneficial[8] . The advances shown here will increase the viability of the LiMIT system in large-scale testing, and allow for extensive design iteration to begin tackling the large powers and heat fluxes present in reactor-relevant systems.